2021
DOI: 10.1073/pnas.2025806118
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) N -heterocyclic carbene complexes arrest metastatic tumor growth

Abstract: Vimentin is a cytoskeletal intermediate filament protein that plays pivotal roles in tumor initiation, progression, and metastasis, and its overexpression in aggressive cancers predicted poor prognosis. Herein described is a highly effective antitumor and antimetastatic metal complex [PtII(C^N^N)(NHC2Bu)]PF6 (Pt1a; HC^N^N = 6-phenyl-2,2′-bipyridine; NHC= N-heterocyclic carbene) that engages vimentin via noncovalent binding interactions with a distinct orthogonal structural scaffold. Pt1a displays vimentin-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The unique properties exhibited by transition-metal complexes as drugs, including their tunability in the oxidation and the coordination states, allow them to enter into many pharmaceutical applications. In the amyloid context, they can be considered as good starting compounds for the development of novel neuroprotective agents. , The stability and inertness of Pt­(II) and Ru­(III) complexes allowed a wide range of investigations with different amyloid systems: phenanthroline (phen)–Pt­(II) complexes with two monodentate ligands ( e.g. , chlorides) inhibit the aggregation of Aβ 1–40 and its N-terminal region as well as of prion protein (PrP) fragments. , Polyoxometalate derivatives of Pt and V suppress amyloid aggregation in a mechanism involving multiple interactions: (i) the coordination of the metal, (ii) electrostatic, (iii) hydrogen, and (iv) van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties exhibited by transition-metal complexes as drugs, including their tunability in the oxidation and the coordination states, allow them to enter into many pharmaceutical applications. In the amyloid context, they can be considered as good starting compounds for the development of novel neuroprotective agents. , The stability and inertness of Pt­(II) and Ru­(III) complexes allowed a wide range of investigations with different amyloid systems: phenanthroline (phen)–Pt­(II) complexes with two monodentate ligands ( e.g. , chlorides) inhibit the aggregation of Aβ 1–40 and its N-terminal region as well as of prion protein (PrP) fragments. , Polyoxometalate derivatives of Pt and V suppress amyloid aggregation in a mechanism involving multiple interactions: (i) the coordination of the metal, (ii) electrostatic, (iii) hydrogen, and (iv) van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%
“…11(a)) with highly efficient in vitro and in vivo anti-tumor and anti-metastatic activities. 77 In their previous study using clickable photoaffinity probes, six potential protein targets were identified for an NHC–gold( iii ) complex that is isostructural to 2-34 through a multi-faceted approach. 78 Herein, the cellular thermal shift assay and immunoblot analysis were further applied to determine the molecular target of 2-34 from those six proteins.…”
Section: Anti-tumor Organometallics Targeting Tumor-specific Biomolec...mentioning
confidence: 99%
“…In contrast to the covalent binding mode of 2-33 with ASNS, molecular dynamics simulation analysis indicated that 2-34 binds with vimentin via noncovalent interactions through its orthogonal scaffold synergistically arranged by both the [Pt(C^N^N)] plane and NHC unit. 77…”
Section: Anti-tumor Organometallics Targeting Tumor-specific Biomolec...mentioning
confidence: 99%
“…Platinum-based drugs have been successfully used in the treatment of various types of cancer in clinic ( Breglio et al, 2017 ; Shaili et al, 2019 ; Karmakar et al, 2020 ; Tham et al, 2020 ; Wan et al, 2021 ). However, these agents exhibit undesired side effects during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%